Effects of recent 0.08% legal blood alcohol limits on fatal crash involvement. Issue 2 (1st June 2000) - Hingson, Ralph; Heeren, Timothy; Winter, Michael
Abstract : Objectives —This study assessed whether states that lowered legal blood alcohol limits from 0.10% to 0.08% in 1993 and 1994 experienced post-law reductions in alcohol related fatal crashes. Methods —Six states that adopted 0.08% as the legal blood alcohol limit in 1993 and 1994 were paired with six nearby states that retained a 0.10% legal standard. Within each pair, comparisons were made for the maximum equal available number of pre-law and post-law years. Results —States adopting 0.08% laws experienced a 6% greater post-law decline in the proportion of drivers in fatal crashes with blood alcohol levels at 0.10% or higher and a 5% greater decline in the proportion of fatal crashes that were alcohol related at 0.10% or higher. Conclusions —If all states adopted the 0.08% legal blood alcohol level, 400–500 fewer traffic fatalities would occur annually.